A Canadian icon in a 'cretinous provincial dump' – Glenn Gould and Thomas Bernhard's novel The Loser. Issue 1 (July 2015) - Blake, Jason
Abstract : This article examines Thomas Bernhard's 1983 The Loser from a 'Canadianist' perspective. Though the Austrian novelist inserted a fictionalised Glenn Gould into his work, he had little interest in the pianist's actual biography and even less interest in Canada. This makes for fascinating reading because one sees an outsider's view of a Canadian icon. Bernhard uses Gould as a tool for attacking Austrian culture. After briefly introducing Bernhard's uniquely complicated relationship to Austria, the article considers how the novelist creatively misuses Gould's biography. It then reflects on Gould's status as a Canadian icon of high culture at a time of great cultural anxiety, as well as on creative opportunities Gould had as a result of his iconic status. Bernhard lost sight of the real Gould, and yet the 'Canadianist' gains a valuable outside view of Canada and European thoughts of Canada when reading this translated work.